Effect of Suplementation Tomatoes Juice in Fresh Semen Egg Yolk Citrate Diluent on the Quality of Spermatozoa and the Success of Artificial Insemination in Thin Tailed Sheep - Safa’atin, Dewi Safitri; Hartati, Puji; Andanawari, Suci; Rosa Zulfikhar; Akbarrizki, Muzizat; Pranatasari, Dewi; Nawangsari, Dwi Novrina; Sukoco, Hendro; Cahyani, Annisa Putri (Jurnal Multidisiplin Madani, 2024)
This study aims to determine the effect of adding tomato juice in fresh semen egg yolk citrate diluent to the quality of spermatozoa and the success of artificial insemination in thin tailed sheep. This research was conducted using a completely randomized design research method with 3 treatments and 5 repetitions. The treatments consisted of a solution of egg yolk citrate (P0), egg yolk citrate added 20% tomato juice (P1), and egg yolk citrate added 40% tomato juice (P2). Data analysis on spermatozoa quality included motility, viability, and abnormality using one way anova followed by Duncan’s test, while artificial insemination success included Non Return Rate (NRR) and Conception Rate (CR) using descriptive analysis. The results showed that the best diluent was found in P1 with the addition of 20% tomato juice resulting in motility percentages and viability are 75,52 ± 1,92 and 87,70 ± 1,04. It can be concluded that the addition of tomato juice had a significant (P<0,05) effect on the motility and viability of spermatozoa. The addition of 20% tomato juice in egg yolk citrate diluent can improve the quality of spermatozoa. The CR and NRR values obtained from artificial insemination with P1 diluent were 53% and 60%